NETWORKING THAT NOT WORKING: CHALLENGES IN INDONESIA’S MARITIME POLICY NETWORK - Dwiputri, Dinar Afina; Bainus, Arry; Widianingsih, Ida (Universitas Padjadjaran, 2024)
Countries with a vast sea area have faced great concern regarding maritime security. Indonesia, a maritime country with an enormous marine resource that contributes 2.58% to the country’s GDP, ranked second as a vulnerable country to marine threats, such as Illegal, Unreported, and Unregulated (IUU) fishing. This research analyzes the implementation of Indonesia’s 2021 – 2025 Maritime Policy Action Plan and how the policy network cooperates to eradicate IUU fishing. Through qualitative content analysis, several regulations and laws in line with the policy action plan were subject to the analysis and reports published by authorized governmental agencies, such as the Indonesian Maritime Security Agency and the Ministry of Marine Affairs and Fishery. Based on policy network analysis of reports by ministries and institutions/agencies, sectoral ego and integration are the critical issues to curb in the policy community. The lack of an integrated system of information sharing has been a part of challenges in collaborative efforts to attain the state of a secure and safe sea. In this regard, the government must strengthen the information-sharing system in their policy network and the policy community itself to maximize efforts on the security of jurisdiction territory to eradicate IUU fishing. Negara dengan wilayah laut yang luas sering kali menghadapi permasalahan terkait keamanan maritim. Indonesia, negara maritim dengan limpahan sumber daya laut yang menyumbang 2,58% terhadap PDB negara, mendapatkan predikat sebagai negara terentan peringkat kedua terhadap ancaman kelautan, seperti Illegal, Unreported, and Unregulated (IUU) fishing. Penelitian ini menganalisis implementasi dari Rencana Aksi Kebijakan Kelautan Indonesia 2021 – 2025 dan melihat bagaimana jejaring kebijakan bekerja untuk ‘memerangi’ IUU fishing. Melalui konten analisis kualitatif, beberapa regulasi dan undang-undang yang sejalan dengan rencana aski kebijakan dan laporan-laporan yang dipulikasikan oleh instansi pemerintah yang berwenang, seperti Badan Keamanan Laut dan Kementerian Kelautan dan Perikanan, juga digunakan untuk dianalisis. Berdasarkan analisis pada jejaring kebijakan dalam laporan-laporan yang dipublikasikan kementerian dan institusi/lembaga, ego sektoral dan integrasi memiliki peran yang penting dalam pencapaian rencana aksi kebijakan. Kurangnya sistem pembagian informasi yang terintegrasi menjadi bagian dari halangan dalam bekerja sama untuk mencapai keadaan laut yang aman. Berkaitan dengan hal tersebut, pemerintah harus meningkatkan sistem berbagi informasi dalam jejaring kebijakan dan policy community-nya sendiri untuk mengoptimalkan upaya dalam pengamanan wilayah yurisdiksi dalam rangka pemberantasan IUU fishing.